Penatalaksanaan Holistik Pasien Diabetes Melitus Pada Wanita Usia 52 Tahun Di Puskesmas Sukamaju Melalui Pendekatan Kedokteran Keluarga - Gantarialdha, Nadya; Zuraida, Reni (CV. Jasa Sukses Abadi, 2024)
Diabetes Mellitus is a degenerative disease with a high prevalence and increasing every year. There is a possibility that there will be an increase in the number of people with Diabetes Mellitus in the future, so that comprehensive management must be carried out which is expected to prevent complications and improve the quality of life of patients. Application of evidence-based medicine-based services to patients by identifying risk factors, clinical problems, and patient management based on a patient-centered problem-solving framework with a patient-centered, family-focused, and community-oriented approach. This study is a case report. Primary data were obtained through anamnesis, physical examination and home visits to assess the physical environment. The assessment is based on a holistic diagnosis of the initial, process, and final studies qualitatively and quantitatively. After the intervention, there was an increase in the knowledge of patients and their families regarding the importance of controlling health workers, taking medication regularly, eating patterns and physical activities that are suitable for people with Diabetes Mellitus. Holistic management has been carried out using the family doctor approach, Mrs. S, 52 years old with Type 2 Diabetes Mellitus adjusted based on initial holistic diagnostics. The interventions carried out have increased patient and family knowledge regarding the importance of control to health workers, regular drug consumption, dietary patterns and physical activity as indicated by improvements in the final holistic diagnostic.